Implications of urbanism for the use of local news media: effects of population concentration on types of news acquisition in Japan. Issue 11 (1st November 2016) - Kitamura, Satoshi
ABSTRACT: The Internet, a global computer network enabling people to send and receive information anywhere in the world, also functions as a local medium of communication. This study focuses on the role of the Internet in transmitting local news and examines the effects of community population concentrations as socio-ecological environments on the use of local news media consumed online and offline. Data from 1367 respondents across 156 Japanese communities were used to analyze the relationships between type of community and type of news source. The findings suggest that people who live in highly populated communities tend more often to use the Internet to access local news, whereas those in less populated communities tend to use more traditional mass media. However, the results of this study did not show a relationship between population concentrations within communities and the acquisition of international news, nor did the social features of residents adequately explain the effects of population concentration on the acquisition of local news. These results are consistent with theoretical predictions based on network externalities, urbanism, and collective action. The findings indicate that local news consumption is embedded in local social contexts in a way that international news is not, reinforcing the importance of urbanism in the information age.